Association of public policy on the management of secondary schools in Kwara State, Nigeria - Oluwalola, K. Felicia; Bello , K. Yunus (Kashere Journal of Education, 2023)
This study examined the association between public policy and the management of secondary schools in Kwara State. The research design adopted for this study was the descriptive research design of survey type. The population for the study was 523 principals in Kwara State secondary schools, and a purposive sampling technique was used to select 333 principals. The instrument used for this study was a researcher-designed questionnaire. The reliability of the instrument was tested using the test-retest method within an interval of four weeks. The data collected was analyzed using Cronbach’s alpha. The analysis of the collected data was done, and a reliability coefficient of 0.84 was obtained. Pearson product moment correlation was used to analyze the hypotheses raised for this study at the 0.05 level of significance. The findings of this study revealed that there was a positive significant relationship between public policy and academic planning (R-value 0.140, p-value = 0.017); between public policy and financial management (R-value 0.140, p-value = 0.023); between public policy and record keeping (R-value 0.140, p-value = 0.021); and between public policy and discipline (R-value 0.140, p-value = 0.015). This study recommended, among others, that school administrators and managers should always be guided by the policy and laid-down rules in decision-making and ensuring effective implementation of policies guiding school management.